The use of anatomy applications as a pedagogical strategy in the morphofunctional laboratory: an experience report (Research, Society and Development, 2022)
Objective: This report aims to describe the experience of using 3D applications made available for free through mobile devices such as tablets and smartphones during practical human anatomy classes. Methodology: this is a descriptive and qualitative study, of the experience report type, which aims to discuss and incite reflections regarding the experiences of students of the basic cycle of the medical course during practical anatomy classes, using free 3D applications, in a private college in the north of Piauí, during the first semester of the year 2020. Results: the use of 3D Anatomy applications expanded the students' three-dimensional anatomical perception, previously limited by the low options of anatomical cuts in synthetic parts and the scarcity of materials organic materials available for dissection. Despite some disadvantages, the interaction between students, learning and academic performance were enhanced, which favored the growth of motivation and interest in learning anatomy on the part of university students. Conclusion: technology allowed an expansion of anatomical visualization, establishing topographical relationships more effectively, which facilitated learning and triggered greater student interest, allowing a self-directed study, developing positive results in the pedagogical scenario. However, there were some limitations, such as difficulty of access, unknown literary base, need for direct monitoring by the professor, need for literature to complement the study, absence of technological devices (smartphones, tablets, computers) and unpreparedness of students and professors to handle these applications.